Effects of dried distillers grains as a replacement for soybean meal in Boer goat diet - Harding, Emma C.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The lack of peer-reviewed, published research evaluating dried distillers grains (DDGS) inclusion in goats limits producers’ ability to utilize the feed ingredient. With the per protein unit cost advantage of DDGS over soybean meal (SBM) being $1.86, this is a missed opportunity for the corn industry, and is becoming even more so due to the rapid growth of the U.S. goat industry over the past 15 years. The objective of this project was to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. 48 meat goat kids were split into pens and assigned to one of four experimental diets. Treatment 1 was 0% SBM replaced by DDGS, treatment 2 was 33% SBM replaced by DDGS, treatment 3 was 66% SBM replaced by DDGS, and treatment 4 was 100% SBM replaced by DDGS. There were 3 kids per pen and 4 pens per treatment. The diets were pelleted and contained roughage, so no supplemental forage was needed, and the goats had constant access to water. These diets were fed for 56 days, and weights were recorded every week to calculate ADG, ADFI, and G:F. The kids were also given 140 mg/hd/d of thiamin to avoid potential polioencephalomalacia. At the end of the experiment, 2 kids per pen were slaughtered, and hot carcass weight, yield, loin eye area, and fat depth at the 13th rib were measured. Data was analyzed using the GLIMMIX procedure of SAS, with pen serving as the experimental unit and P-value ≤ 0.05 considered significant. The results showed that there was no statistical difference between the goats fed the different diets for ADFI (P=0.346), ADG (P=0.092), hot carcass weight (P=0.674), yield (P=0.478), loin eye area (P=0.505), or fat depth (P=0.977). The G:F ratio for treatment 4 was statistically significantly higher than that for treatment 1 (P=0.001). Overall, these results indicate that including DDGS in a goat diet will result in financial savings without having any negative impacts on the growth or carcass characteristics of Boer goats.
Keywords: Spring 2018